The Flotation of Alluvial Gold - S G. Keyte (The Australasian Institute of Mining and Metallurgy, 1990)
Gravity methods of recovering alluvial gold are not very efficient at particle sizes below about 0.l mm. Whereas such gold may not have been economic to recover in the past, the same may not be true today. Centrifugal concentrators, like the Knudsen and Knelson bowls, are showing promise after an inauspicious start, at least in New Zealand. The large proportion of heavy mineral in many auriferous beach sands and the natural hydrophobicity of fine gold should make flotation an attractive contender for its recovery. The conventional mechanical flotation cell is effective, but roughing, scavenging and cleaning are necessary to achieve both high recovery and low mass Yield. More problematic is the difficulty of maintaining coarse and dense sands in suspension. The air sparged hydrocyclone is effective at recovering fine gold from a fine Colarado River sand, but is not effective for the coarse and dense beach sands of New Zealand. The flotation column shows much promise for these sands, when recoveries of over 80 per cent and mass yields of less than one per cent can be achieved in a single pass. The froth separator of the USSR and flash flotation could also be worthy contenders. It is felt that flotation could be limited to naturally and artificially de-slimed concentrates.